Prophylactic vaccines are potent activators of monocyte-derived dendritic cells and drive effective anti-tumor responses in melanoma patients at the cost of toxicity - Bol, Kalijn F. (Cancer Immunol Immunother, 2016)
Dendritic cell (DC)-based immunotherapy is explored worldwide in cancer patients, predominantly with DC matured with pro-inflammatory cytokines and prostaglandin E(2). We studied the safety and efficacy of vaccination with monocyte-derived DC matured with a cocktail of prophylactic vaccines that contain clinical-grade Toll-like receptor ligands (BCG, Typhim, Act-HIB) and prostaglandin E(2) (VAC-DC). Stage III and IV melanoma patients were vaccinated via intranodal injection (12 patients) or combined intradermal/intravenous injection (16 patients) with VAC-DC loaded with keyhole limpet hemocyanin (KLH) and mRNA encoding tumor antigens gp100 and tyrosinase. Tumor antigen-specific T cell responses were monitored in blood and skin-test infiltrating-lymphocyte cultures. Almost all patients mounted prophylactic vaccine- or KLH-specific immune responses. Both after intranodal injection and after intradermal/intravenous injection, tumor antigen-specific immune responses were detected, which coincide with longer overall survival in stage IV melanoma patients. VAC-DC induce local and systemic CTC grade 2 and 3 toxicity, which is most likely caused by BCG in the maturation cocktail. The side effects were self-limiting or resolved upon a short period of systemic steroid therapy. We conclude that VAC-DC can induce functional tumor-specific responses. Unfortunately, toxicity observed after vaccination precludes the general application of VAC-DC, since in DC maturated with prophylactic vaccines BCG appears to be essential in the maturation cocktail. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00262-016-1796-7) contains supplementary material, which is available to authorized users.